Basion–Cartilaginous Dens Interval: An Imaging Parameter for Craniovertebral Junction Assessment in Children - Singh, A.K.; Fulton, Z.; Tiwari, R.; Zhang, X.; Lu, L.; Altmeyer, W.B.; Tantiwongkosi, B. (American Journal of Neuroradiology, 2017)
BACKGROUND AND PURPOSE: Widening of the basion-dens interval is an important sign of cranioverterbral junction injury. The current literature on basion-dens interval in children is sparse and based on bony measurements with variable values. Our goal was to establish the normal values of a recently described new imaging parameter, the basion–cartilaginous dens interval in children.MATERIALS AND METHODS: Three hundred healthy pediatric patients (0–10 years of age) were selected retrospectively. These patients were divided into 3 different groups: A (0–3 years), B (3–6 years), and C (6–10 years). The basion–cartilaginous dens interval was calculated on the sagittal MPR image of cervical spine CT in a soft-tissue window. The mean, SD, and the upper limit of normal (mean +2 SDs) of the 3 groups were calculated, and statistical tests were used to check for significant differences of the basion–cartilaginous dens interval among these 3 groups.RESULTS: The upper limits of the basion–cartilaginous dens interval for the 3 groups were 5.34 mm in group A, 5.64 mm in group B, and 7.24 mm in group C. There were statistically significant differences in the basion–cartilaginous dens interval values among the 3 groups. There was no statistically significant difference in basion–cartilaginous dens interval values between groups A and B; however, values in group C were significantly different from those in both A and B. There was no statistically significant difference in the basion–cartilaginous dens interval values between males and females.CONCLUSIONS: The basion–cartilaginous dens interval is a novel imaging parameter to assess cranioverterbral junction integrity in children, which includes the nonossified cartilage in the measurement.BDIbasion-dens intervalBCDIbasion–cartilaginous dens intervalCVJcraniovertebral junction